Scandinavian blue : the erotic cinema of Sweden and Denmark in the 1960s and 1970s - Stevenson, Jack, 1955- (McFarland & Co, 2010)
"This book traces the development of Scandinavian erotic cinema as it evolved in Denmark and Sweden and gauges the influence it had on other countries, particularly the U.S. where it helped to set in motion the sexual revolution and contributed to the end of film censorship"--Provided by publisher.